Frequency and wavelength tunable optical microwave source based on a distributed Bragg reflector self-pulsation laser - 刘扬 孙瑜 孔端花 王宝军 边静 安欣 赵玲娟 王圩 (Journal of semiconductors, 2010)
A frequency and wavelength tunable self-pulsation laser based on DBR laser devices is reported for the first time.This laser generates continuous tunable optical microwave in the range of 1.87-21.81 GHz with 3-dB linewidth about 10 MHz by tuning the injection currents on the front and back gain sections,and exhibits wavelength tuning range from 1536.28 to 1538.73 nm by tuning the injection currents on the grating section.